IMPLEMENTASI DIGITAL MARKETING TERHADAP PENINGKATAN PENJUALAN HASIL HOME INDUSTRI - Ratna Gumilang, Risa (Coopetition : Jurnal Ilmiah Manajemen, 2019)
Development of information technology is developing very faster now influencing the community in supporting various business activities both large and small to be known globally. The most obvious impact is not only being known but also increasing the volume of sales and profits. Digital Marketing is one of the very large marketing media that has an influence. By using digital marketing in this case is social media, sculpture carvings from Cipacing Bandung market the results of home industry in the form of handicrafts from a piece of unused wood carved into a unique sculpture. Initially this activity was only as a free time, but at this time it became the main activity as an increase in economic turnover in the household. Formerly the sales activities of these industrial products were conventional and traditional, they make products only on order. But after getting to know about the existence of some social cipacing residents, they have started to receive a lot of orders, so the sales volume is increasing faster compared to when selling with the old way. Digital marketing is seen as the best media as the most effective and efficient promotional tool and able to increase sales volume significantly.